Haematopoietic stem cell transplantation for mucopolysaccharidosis type VII: A case report. (9th August 2018) - Sisinni, Luisa; Pineda, Mercedes; Coll, Maria Josep; Gort, Laura; Turon, Eulalia; Torrent, Montserrat; Ey, Anna; Tobajas, Eva; Badell, Isabel
Abstract: Mucopolysaccharidosis type VII (MPS VII) is an inherited disease characterized by the cellular accumulation of undegraded GAGs due to the deficiency of the lysosomal enzyme β‐glucuronidase. We describe a case of a 2‐year‐old female affected by a moderate form of MPS VII and submitted twice to HSCT with the aim of stabilizing skeletal problems and preventing neurocognitive alterations. The child underwent a second transplantation due to the rejection of the graft after a reduced‐intensity conditioning in the first transplant. A myeloablative regimen allowed to achieve a stable full donor engraftment and normal enzyme levels during the 6 years of follow‐up. Clinically, we observed stabilization of skeletal deformities and normal neurocognitive development. This is one of the few reports of mucopolysaccharidosis type VII treated with allogeneic HSCT.